Application of wire arc additive manufacturing for repair of Monel alloy components. Issue 5 (20th October 2021) - Marenych, O.O.; Kostryzhev, A.G.; Pan, Z.; Li, H.; van Duin, S.
ABSTRACT: Monel alloys containing 63Ni-30Cu-2.0Mn-2.0Fe-AlTiC (wt. %) are often used for manufacturing of machine parts in marine, chemical, and oil extraction industries. Despite excellent corrosion resistance and mechanical properties, Monel components may fail via wear, which is enhanced in corrosive environment. Heavy components working under high loads may experience galling, which is welding followed by tearing of large pieces of material off the contacting surfaces. In addition to high cost of Ni-based alloys, heavy parts of machinery may not be easily replaced, and, thus, require repair being in partial assembly. In this paper, we introduce wire arc additive manufacturing (WAAM) technology as a repair method for Monel alloy components. The effect of post-weld heat treatment on microstructure and hardness of both the component body and the repair layer is investigated and discussed.